Nature-Based Meditation Reduces Depressive Rumination and Stress in Adolescents and Young Adults - Matthew Owens; Hannah L. I. Bunce (Psychiatry International, 2025)
Nature-based interventions (NBIs) grounded in mindfulness have been shown to be beneficial for improving mental wellbeing in adults. With increasing mental health challenges among children and adolescents, accessible and cost-effective interventions are essential to enhance their well-being. Brief mindfulness-based NBIs may be helpful in this regard, but there is a dearth of evidence testing such NBIs in young adolescents. The aim of this study was to test the effect of a brief nature-based meditation on mental wellbeing in community groups of adolescents (n = 38; aged 12–17) and adults (n = 39; aged 18–26). We hypothesised that the meditation would reduce depressive rumination and stress in both age groups. In a repeated-measures design, participants completed self-report measures, indexing mental wellbeing (state rumination and stress) before and immediately after listening to a brief (13 min) nature-based meditation. Rumination and stress improved overall, and the pattern in the data suggested that effects were larger for adults when compared to adolescents. This study provides preliminary evidence for the use of a brief nature-based meditation in improving mental wellbeing in adolescents. Future research should make NBIs age appropriate and examine their effectiveness for clinical adolescent populations.